Disunited nations : the scramble for power in an ungoverned world - Zeihan, Peter (Harper Business, an imprint of HarperCollinsPublishers, 2020)
"Most countries and companies are not prepared for the world Peter Zeihan says we're already living in. For decades, America's allies have depended on its might for their economic and physical security. But as a new age of American isolationism dawns, the results will surprise everyone. In Disunited Nations, geopolitical strategist Peter Zeihan presents a series of counterintuitive arguments about the future of a world where trade agreements are coming apart and international institutions are losing their power"--